A method for producing a basalt fiber reinforced photovoltaic module
Through the hot-press forming of titanium-modified basalt fibers and epoxy resin, combined with grafting technology and diammonium titanium coating, the problem of insufficient strength and durability of fiber reinforced composite materials is solved, and the performance and application range of photovoltaic modules are significantly improved.
Patent Information
- Application Number
- CN202411096249.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The tensile strength, bending strength and aging resistance of existing fiber reinforced composites limit their application range.
Titanium modified basalt fibers and epoxy resins are used for hot pressing to form a basalt fiber composite material, and benzophenone structure and diammonium titanium coating are introduced through grafting technology to enhance the photoactivity and interface stability of the material.
It significantly improves the mechanical strength, photoelectric conversion efficiency and durability of photovoltaic modules, and expands its application range.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic components, in particular to a production method of a basalt fiber reinforced photovoltaic component. Background Art
[0002] Single solar cells cannot be used directly as power sources. To be used as power sources, several single cells must be connected in series and parallel and tightly sealed into components. Photovoltaic components (also called solar panels) are the core part of solar power generation systems and the most important part of solar power generation systems. Their function is to convert solar energy into electrical energy and send it to batteries for storage or to drive loads.
[0003] Chinese patent CN115991933A: provides a fiber-reinforced composite photovoltaic module frame. The raw materials of the photovoltaic module frame include, by total weight: 30-45% of a resin mixture and 55-70% of fibers; the components of the resin mixture include: by weight, 80-120 parts of a base resin, 1-4 parts of a curing agent, 1-3 parts of a lubricant, 5-15 parts of a flame retardant, 0.5-3 parts of a dispersant, and 5-35 parts of an inorganic filler.
[0004] Chinese patent CN114889272A: discloses a low-cost flexible photovoltaic module and its preparation method, the photovoltaic module includes a battery string, a front plate arranged on the light-receiving surface of the battery string, a back plate arranged on the backlight surface of the battery string, and a wire box; the front plate and the back plate are respectively compounded with the battery string through a second adhesive layer and a third adhesive layer; the wire box is installed on the light-receiving surface of the front plate, and a hole is opened in the middle of the front plate to connect the battery string lead wire to the wire box; the front plate includes a fluorine film and a modified FRP plate, and the fluorine film and the modified FRP plate are compounded through a first adhesive layer; the modified FRP plate is composed of a reinforcing material and a base material, and the base material impregnates the reinforcing material.
[0005] Chinese patent CN103205004A: discloses a composite material profile and its preparation method and application in the preparation of solar photovoltaic modules. The composite material profile is composed of fiber reinforcement and resin, the mass ratio of the fiber reinforcement to the resin is 6-9:1-4; the fiber reinforcement is a mixture of mixed fiber and mixed fiber fabric.
[0006] According to the existing public technical records, the tensile strength and flexural strength of fiber-reinforced composite materials prepared are still insufficient, and there is also a large room for improvement in aging resistance, which restricts its scope of application. Summary of the invention
[0007] In view of the above problems existing in the prior art, the object of the present invention is to provide a method for producing a basalt fiber reinforced photovoltaic module.
[0008] In order to solve the above technical problems, the technical solution of the present invention is:
[0009] In the first aspect, a method for producing a basalt fiber reinforced photovoltaic module comprises the following steps:
[0010] S1: put 60-70 parts of titanium modified basalt fiber into 30-50 parts of resin mixture and impregnate for 20-40 minutes;
[0011] S2: placing the impregnated titanium-modified basalt fiber into a mold, hot pressing, cooling and demoulding, to obtain a basalt fiber composite material;
[0012] In some embodiments of the present invention, the resin mixture comprises 80-100 parts of epoxy resin E51, 5-10 parts of curing agent, 1-3 parts of accelerator, and 10-20 parts of inorganic filler.
[0013] In some embodiments of the present invention, the photovoltaic module is arranged in a frame structure; a photovoltaic slot is provided on the top of the frame body, and the photovoltaic module is inserted into the photovoltaic slot; the upper frame, lower frame, side frame and corner code of the photovoltaic module are all made of basalt fiber composite materials.
[0014] In some embodiments of the present invention, the curing agent is one of dimethyl phthalate, diethylene glycol, cumene hydroperoxide, methyl ethyl ketone peroxide, benzoyl peroxide, and 2-ethyl-4-methylimidazole.
[0015] In some embodiments of the present invention, the accelerator is cobalt isooctanoate.
[0016] In some embodiments of the present invention, the inorganic filler is calcium carbonate or aluminum hydroxide.
[0017] In some embodiments of the present invention, the hot pressing step is: curing at 60-70°C and 1 MPa for 120-150 min; curing at 80-90°C and 1 MPa for 90-120 min; curing at 130-140°C and 1 MPa for 200-240 min.
[0018] In the second aspect, the preparation method of the titanium modified basalt fiber is:
[0019] T1: Before the reaction starts, nitrogen is used to replace oxygen in the reaction system, 100-120 parts of basalt fiber, 3-6 parts of (γ-isocyanatepropyl)trimethoxysilane, and 1000-1200 parts of isopropanol are weighed out, and the reaction mixture is heated at 60-70°C and maintained for 100-150 minutes;
[0020] T2: Add 4-8 parts of 2,2',4,4'-tetrahydroxybenzophenone, 0.004-0.08 parts of di(2-hydroxypropionic acid) diammonium dihydroxide titanium (CAS: 5104-06-5), and 0.5-2 parts of stannous octoate, heat at 60-70°C and keep for 30-100 minutes, cool to room temperature, filter, and dry to obtain titanium-modified basalt fiber.
[0021] The reaction mechanism of this method is as follows:
[0022] 1. Chemical structure analysis: In basalt fiber, the isocyanate group (-NCO) in graphene has a strong positive charge due to its electronic resonance structure, and the carbon atom becomes an electrophilic center, while the oxygen atom becomes a nucleophilic center due to its high electronegativity.
[0023] 2. Nucleophilic addition reaction: Di(2-hydroxypropionic acid) diammonium dihydroxide titanium, the hydroxyl group of 2,2',4,4'-tetrahydroxybenzophenone acts as a nucleophilic reagent to attack the partially positively charged carbon atom in the isocyanate group, resulting in a nucleophilic addition reaction to form a stable urethane bond connection.
[0024] The present invention provides a method for producing a basalt fiber-reinforced photovoltaic module. Compared with the prior art, the present invention has the following significant effects:
[0025] 1. Enhanced photoactivity: Through grafting technology, the introduced benzophenone structure enhances the photoactivity of the material surface, helps to improve the efficiency of UV curing, and can significantly improve product performance when used in the preparation of photovoltaic modules; the thermal responsiveness and photosensitivity of the material can be increased through surface modification, which is particularly important in the fields of biomedicine and optoelectronic materials.
[0026] 2. Enhanced interface stability: Grafted diammonium titanium can form a stable quaternary ammonium salt coating on the surface of the material. This coating is connected to the substrate through covalent bonds, providing excellent interface stability and durability.
[0027] 3. Improvement of composite material performance: Graphene is widely used to enhance composite materials due to its excellent physical properties. Grafting technology can better achieve its dispersion in the matrix material and avoid aggregation, thereby maximizing its enhancement effect. It can also achieve functional modification of graphene and further broaden its application in energy, sensing and other fields.
[0028] In summary, in practical applications, these technical effects not only improve the basic properties of materials, but also give them new functions, greatly expanding their scope of application; in the manufacture of photovoltaic modules, while using toughened epoxy resin, by adding modified basalt fiber, not only the mechanical strength of the module is improved, but also the addition of graphene and diammonium titanium improves the photoelectric conversion efficiency and product durability; the development and application of these technologies demonstrate the growing influence of materials science in modern science and technology. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof. The present invention is further described below in conjunction with the embodiments. Example
[0031] A method for producing a basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0032] S1: 60g of titanium-modified basalt fiber was placed in 30g of resin mixture and immersed for 20min;
[0033] S2: placing the impregnated titanium-modified basalt fiber into a mold, hot pressing, cooling and demoulding, to obtain a basalt fiber composite material;
[0034] The resin mixture is 80g of epoxy resin E51, 5g of curing agent, 1g of accelerator, and 10g of inorganic filler.
[0035] The photovoltaic module is arranged in the frame structure; a photovoltaic slot is arranged on the top of the frame body, and the photovoltaic module is inserted into the photovoltaic slot; the upper frame, lower frame, side frame and corner code of the photovoltaic module are all made of basalt fiber composite materials.
[0036] The curing agent is dimethyl phthalate.
[0037] The accelerator is cobalt isooctanoate.
[0038] The inorganic filler is calcium carbonate.
[0039] The hot pressing steps are: curing at 60°C and 1MPa for 120 minutes; curing at 80°C and 1MPa for 90 minutes; and curing at 130°C and 1MPa for 200 minutes.
[0040] The preparation method of the titanium modified basalt fiber is as follows:
[0041] T1: Before the reaction started, nitrogen was used to replace oxygen in the reaction system, 100 g of basalt fiber, 3 g of (γ-isocyanatepropyl)trimethoxysilane, and 1000 g of isopropanol were weighed out, and the reaction mixture was heated at 60 °C for 100 minutes;
[0042] T2: Add 4g 2,2',4,4'-tetrahydroxybenzophenone, 0.004g di(2-hydroxypropionic acid) diammonium dihydroxide titanium (CAS: 5104-06-5), and 0.5g stannous octoate, heat at 60°C and keep for 30 minutes, cool to room temperature, filter, and dry to obtain titanium-modified basalt fiber. Example
[0043] A method for producing a basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0044] S1: 63g of titanium-modified basalt fiber was placed in 35g of resin mixture and impregnated for 25min;
[0045] S2: placing the impregnated titanium-modified basalt fiber into a mold, hot pressing, cooling and demoulding, to obtain a basalt fiber composite material;
[0046] The resin mixture is 85g of epoxy resin E51, 6g of curing agent, 2g of accelerator, and 13g of inorganic filler.
[0047] The photovoltaic module is arranged in the frame structure; a photovoltaic slot is arranged on the top of the frame body, and the photovoltaic module is inserted into the photovoltaic slot; the upper frame, lower frame, side frame and corner code of the photovoltaic module are all made of basalt fiber composite materials.
[0048] The curing agent is diethylene glycol.
[0049] The accelerator is cobalt isooctanoate.
[0050] The inorganic filler is calcium carbonate.
[0051] The hot pressing steps are: curing at 65°C and 1MPa for 130 minutes; curing at 85°C and 1MPa for 100 minutes; and curing at 135°C and 1MPa for 210 minutes.
[0052] The preparation method of the titanium modified basalt fiber is as follows:
[0053] T1: Before the reaction started, nitrogen was used to replace oxygen in the reaction system, 105 g of basalt fiber, 4 g of (γ-isocyanatepropyl)trimethoxysilane, and 1050 g of isopropanol were weighed out, and the reaction mixture was heated at 65 °C for 110 minutes;
[0054] T2: Add 5g 2,2',4,4'-tetrahydroxybenzophenone, 0.02g di(2-hydroxypropionic acid) diammonium dihydroxide titanium (CAS: 5104-06-5), and 1g stannous octoate, heat at 65°C and keep for 50 minutes, cool to room temperature, filter, and dry to obtain titanium-modified basalt fiber. Example
[0055] A method for producing a basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0056] S1: 68g of titanium-modified basalt fiber was placed in 45g of resin mixture and impregnated for 35min;
[0057] S2: placing the impregnated titanium-modified basalt fiber into a mold, hot pressing, cooling and demoulding, to obtain a basalt fiber composite material;
[0058] The resin mixture is 95g of epoxy resin E51, 8g of curing agent, 2g of accelerator, and 18g of inorganic filler.
[0059] The photovoltaic module is arranged in the frame structure; a photovoltaic slot is arranged on the top of the frame body, and the photovoltaic module is inserted into the photovoltaic slot; the upper frame, lower frame, side frame and corner code of the photovoltaic module are all made of basalt fiber composite materials.
[0060] The curing agent is cumene hydroperoxide.
[0061] The accelerator is cobalt isooctanoate.
[0062] The inorganic filler is aluminum hydroxide.
[0063] The hot pressing steps are: curing at 65°C and 1MPa for 140 minutes; curing at 85°C and 1MPa for 110 minutes; and curing at 135°C and 1MPa for 230 minutes.
[0064] The preparation method of the titanium modified basalt fiber is as follows:
[0065] T1: Before the reaction started, nitrogen was used to replace oxygen in the reaction system, 115 g of basalt fiber, 5 g of (γ-isocyanatepropyl)trimethoxysilane, and 1150 g of isopropanol were weighed out, and the reaction mixture was heated at 65 °C and maintained for 140 minutes;
[0066] T2: Add 7g 2,2',4,4'-tetrahydroxybenzophenone, 0.06g di(2-hydroxypropionic acid) diammonium dihydroxide titanium CAS: 5104-06-5, and 1.5g stannous octoate, heat at 65°C and maintain for 80 minutes, cool to room temperature, filter, and dry to obtain titanium-modified basalt fiber. Example
[0067] A method for producing a basalt fiber reinforced photovoltaic module, the operating steps of which are:
[0068] S1: 70g of titanium-modified basalt fiber was placed in 50g of resin mixture and impregnated for 40min;
[0069] S2: placing the impregnated titanium-modified basalt fiber into a mold, hot pressing, cooling and demoulding, to obtain a basalt fiber composite material;
[0070] The resin mixture is 100g of epoxy resin E51, 10g of curing agent, 3g of accelerator, and 20g of inorganic filler.
[0071] The photovoltaic module is arranged in the frame structure; a photovoltaic slot is arranged on the top of the frame body, and the photovoltaic module is inserted into the photovoltaic slot; the upper frame, lower frame, side frame and corner code of the photovoltaic module are all made of basalt fiber composite materials.
[0072] The curing agent is 2-ethyl-4-methylimidazole.
[0073] The accelerator is cobalt isooctanoate.
[0074] The inorganic filler is aluminum hydroxide.
[0075] The hot pressing steps are: curing at 70°C and 1MPa for 150 minutes; curing at 90°C and 1MPa for 120 minutes; and curing at 140°C and 1MPa for 240 minutes.
[0076] The preparation method of the titanium modified basalt fiber is as follows:
[0077] T1: Before the reaction started, nitrogen was used to replace oxygen in the reaction system, 120 g of basalt fiber, 6 g of (γ-isocyanatepropyl)trimethoxysilane, and 1200 g of isopropanol were weighed out, and the reaction mixture was heated at 70 °C and maintained for 150 minutes;
[0078] T2: Add 8g of 2,2',4,4'-tetrahydroxybenzophenone, 0.08g of di(2-hydroxypropionic acid)diammonium dihydroxide titanium (CAS: 5104-06-5), and 2g of stannous octoate, heat at 70°C and keep for 100 minutes, cool to room temperature, filter, and dry to obtain titanium-modified basalt fiber.
[0079] Comparative Example 1
[0080] The basalt fiber is not modified, and the rest is the same as in Example 1.
[0081] Comparative Example 2
[0082] The other steps were the same as in Example 1 except that 2,2',4,4'-tetrahydroxybenzophenone was not added.
[0083] Comparative Example 3
[0084] The other steps were the same as in Example 1 except that titanium di(2-hydroxypropionic acid) diammonium dihydroxide was not added.
[0085] Example test:
[0086] Tensile strength: tested in accordance with GB / T1447-2005;
[0087] Bending strength: Tested in accordance with GB / T1449-2005;
[0088] Aging resistance: Tested in accordance with GB / T2573-2008.
[0089] Test results:
[0090]
[0091] Through the data analysis of the above embodiments and comparative examples, the basalt fiber reinforced photovoltaic module material prepared in the present invention not only has excellent mechanical strength, but also has good durability.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for producing a basalt fiber reinforced photovoltaic module, the operating steps of which are: S1: According to the mass fraction, 60-70 parts of titanium-modified basalt fiber are placed in 30-50 parts of the resin mixture and impregnated for 20-40 minutes; S2: placing the impregnated titanium-modified basalt fiber into a mold, hot pressing, cooling and demoulding, to obtain a basalt fiber composite material; The resin mixture is 80-100 parts of epoxy resin E51, 5-10 parts of curing agent, 1-3 parts of accelerator, and 10-20 parts of inorganic filler; The photovoltaic module is arranged in the frame structure; a photovoltaic slot is arranged on the top of the frame structure, and the photovoltaic module is inserted into the photovoltaic slot; the upper frame, lower frame, side frame and corner bracket of the photovoltaic module are all made of basalt fiber composite materials; The preparation method of the titanium modified basalt fiber is as follows: T1: Before the reaction starts, nitrogen is used to replace oxygen in the reaction system, 100-120 parts of basalt fiber, 3-6 parts of (γ-isocyanatepropyl)trimethoxysilane, and 1000-1200 parts of isopropanol are weighed out, and the reaction mixture is heated at 60-70°C and maintained for 100-150 minutes; T2: Add 4-8 parts of 2,2',4,4'-tetrahydroxybenzophenone, 0.004-0.08 parts of di(2-hydroxypropionic acid) diammonium dihydroxide titanium, and 0.5-2 parts of stannous octoate, heat at 60-70°C and maintain for 30-100 minutes, cool to room temperature, filter, and dry to obtain titanium-modified basalt fiber.
2. The method for producing a basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The curing agent is one of dimethyl phthalate, diethylene glycol, cumene hydroperoxide, methyl ethyl ketone peroxide, benzoyl peroxide, and 2-ethyl-4-methylimidazole.
3. The method for producing a basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The accelerator is cobalt isooctanoate.
4. The method for producing a basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The inorganic filler is calcium carbonate or aluminum hydroxide.
5. The method for producing a basalt fiber reinforced photovoltaic module according to claim 1, characterized in that: The hot pressing steps are: curing at 60-70°C and 1MPa for 120-150min; curing at 80-90°C and 1MPa for 90-120min; curing at 130-140°C and 1MPa for 200-240min.
Citation Information
Patent Citations
Composite material section bar as well as preparation method and application thereof in preparation of solar photovoltaic module
CN103205004A
Low-cost flexible photovoltaic module and preparation method thereof
CN114889272A
Fiber reinforced composite material photovoltaic module frame and preparation method thereof
CN115991933A
Nanometer antibacterial composite material for abdominal muscle board and preparation method thereof
CN107236246A
Preparation method of fiber reinforced composite
CN111363989A